Investigation of epistemological indicators in socio-political talk shows of Iran TV from the perspective of critical discourse [In Persian] - Davood Madani (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2021)
Learning analysis is performed using meta-discourse markers. Learning markers are, in fact, linguistic forms that are considered as important rhetorical tools and ensure interaction in texts. Different models for learning analysis are presented. the Highland pattern is one of the most common and popular. For the first time, Highland has defined and categorized all aspects of the interaction between the author of the text and the wisdom of the text, as well as the author of the text and the reader of the text, using the term learning, and claims that the researcher can go beyond text and discourse and also analyze the text as a social action. Learning is used as a concept in discourse analysis and is used in the interaction between authors and their text between writer and reader. Overall, learning, as an important tool in facilitating communication, helps the writer to communicate with drivers and express his personal findings, as propositions place their relevant sentences or phrases in creating a coherent discourse in the field of text structure. The present article examines the epistemological indicators in socio-political talk shows on the Islamic Republic of Iran TV channels from the perspective of critical discourse based on the views of Highland (2005) and Fairclough (2001). In this research, 20 programs of socio-political talk show of channels 1, 2, 3 and 4 were selected, studied and analyzed qualitatively and quantitatively in a numerical manner using purposive sampling. The variables studied in this study include the gender of the experts, whether the programs are live or recorded, the number of experts in the program, whether they are academics or non-academics to determine the results showed that the distribution of epistemological elements, certainty, skepticism and attitude In socio-political roundtable programs on the Islamic Republic of Iran Broadcasting, it varies according to the gender of the experts, whether the program is live or recorded, whether the experts are academic or non-academic, or the presence of one or more experts in the program. The type of application of epistemological tools in the discourse of experts can be justified.